Respuesta :

Answer: 1=x


Step-by-step explanation:

                                6x+9=3x+6                                                                                                      -6         -6        

                                    6x+3=3x                                                                                               -6x   -6x      3=-3x                                                                                  3 divided by 3 is one    1=x                         I hope this helps sorry if its incorrect i havent done this in a while

Answer:

x = -1

Step-by-step explanation:

Subtract 3x from both sides

6x + 9 - 3x = 3x + 6 - 3x

3x + 9 = 6

Subtract 9 from both sides

3x + 9 - 9 = 6 - 9

3x = -3

Divide both sides by 3

3x/3 = -3/3

x = -1